Comparison of Experimental and Empirical Approaches for Determination of Sound Absorption Properties of Bagasse and Cornhusk Fibers. Issue 14 (28th October 2022) - Taban, Ebrahim; Amininasab, Somayeh; Mehrzad, Shahrzad; Fattahi, Monireh; Tajik, Leila; Samaei, Seyed Ehsan
ABSTRACT: The significant physical, economic and environmental properties of some agricultural wastes have made them viable alternatives for the conventional sound-absorbing materials. Therefore, it is necessary to identify these types of agricultural wastes and investigate the acoustic behavior and applicability of mathematical predictive models for sound absorption of the samples fabricated from such wastes. In this regard, this study was conducted to investigate the sound absorption coefficient (SAC) values of the samples made from sugarcane and corn husk wastes using experimental and empirical methods. The morphological examination of sugarcane and corn husk fibers was performed by Field emission scanning electron microscopy (FESEM). Having prepared the fibers, several cylindrical samples with a constant density (150 kg/m3) and different thicknesses (20, 30 and 40 mm) were fabricated. The SAC values, porosity and airflow resistivity of these samples were then measured using ISO 10534–2 (impedance tube system), SEM and ASTM C522–03, respectively. The Delany-Bazley (DB) analytical model and the reversed Delany-Bazley model with Nelder-Mead Simplex (DB-NMS) were also used to predict the SAC values. Based on the acoustic performance of the fabricated samples, the SAC values for the thickness of 40 mm and frequency of 500 Hz were, respectively, 0.42 and 0.54 for sugarcane and corn. Increasing the thickness of the samples and creating an air gap behind them were found to be the acceptable approaches for improving the sound absorption. It was found that the DB-NMS model would appropriately follow the experimental results. The purposeful application of agricultural waste and analytical acoustic models because of their outstanding benefits and an effective approach will encourage the usability of natural materials (as eco-friendly, cheap and efficient acoustic products) in indoor and outdoor commercial applications.